Purification and structural characterization of the voltage-sensor domain of the hERG potassium channel - Ng, Hui Qi (2013)
The hERG (human ether à go-go related gene) potassium channel is a voltage-gated potassium channel playing important roles in the heart by controlling the rapid delayed rectifier potassium current. The hERG protein contains a voltage-sensor domain (VSD) that is important for sensing voltage changes across the membrane. Mutations in this domain contribute to serious heart diseases. To study the structure of the VSD, it was over-expressed in Escherichia coli and purified into detergent micelles. Lyso-myristoyl phosphatidylglycerol (LMPG) was shown to be a suitable detergent for VSD purification and folding. Secondary structural analysis using circular dichroism (CD) spectroscopy indicated that the purified VSD in LMPG micelles adopted α-helical structures. Purified VSD in LMPG micelles produced dispersed cross-peaks in a 15N-HSQC spectrum. Backbone resonance assignments for residues from transmembrane segments S3 and S4 of VSD also confirmed the presence of α-helical structures in this domain. Our results demonstrated that structure of VSD can be investigated using NMR spectroscopy.